Awakening The Earth: Exploring The Power of Awareness in Soil Health and Environmental Sustainability - Hussain, Moon Moon; Borah, Rashmi Rekha; Bhuvaneswari, G. (Journal of Neonatal Surgery, 2025)
Soil, humble and often unseen, is one of the most precious gifts of nature, quietly nurturing life from beneath our feet. It is the silent foundation upon which our world depends, enabling the growth of plants that feed us, clothe us, and fuel our lives. More than just a medium for roots, soil is a powerful ally in the fight against climate change, holding more carbon than all the forests on Earth combined. It breathes life into the planet through its rich and intricate ecosystems, teeming with biodiversity we barely begin to understand. Despite its immense importance, soil remains a forgotten hero in many climate conversations; perhaps because it is everywhere, we simply overlook its value. While research on soil security is steadily growing, awareness and public understanding still lag behind. To heal and preserve this essential resource amidst the growing threat of climate change, we must embrace a new way of thinking; one that honours soil as a living, breathing part of our planet. This work seeks to illuminate the path forward by exploring sustainable practices that can restore soil health on a global scale. But knowledge alone is not enough. Only through cross-disciplinary collaboration, meaningful communication, and heartfelt public engagement can we bridge the gap between science and action. Soil needs supportive policies to thrive; policies need people’s voices; and those voices can only rise through awareness. This paper reviews some significant research related to soil and is a humble call to awaken to the quiet power beneath us; a reminder that the story of soil is, in many ways, the story of our own survival